Inappropriately Firing Defibrillator: A Simulation Case for Emergency Medicine Residents - Rachel Lauren Thorpe; Namit Rohant; Michael Cryer; Christopher Gainey (Association of American Medical Colleges, 2019)
Introduction Emergency physicians must be able to manage inappropriately firing defibrillators. Many physicians may not experience this high-risk, low-frequency patient presentation during residency. We created this simulation to increase residents' knowledge of basic defibrillator function and confidence in managing patients with malfunctioning defibrillators. Methods Sixteen emergency medicine residents of all levels of training participated in this curriculum. The educational experience began with a lecture. Residents then managed the simulated patient encounter in groups of four. The patient was a 63-year-old male presenting after feeling his defibrillator fire. He was found to have a supraventricular tachycardia with an inappropriately firing defibrillator. Learners needed to recognize the inappropriately firing defibrillator, inactivate it with a magnet, and treat the arrhythmia. Implementation of this scenario required audiovisual equipment and a simulation room equipped with high-fidelity simulator, patient monitor, code cart, defibrillator, and pacemaker magnet. Learners completed pre- and postcourse surveys to assess changes in baseline knowledge of defibrillator function and self-reported confidence in managing these complicated patients. Results After participating in this educational intervention, residents improved their performance on a 10-question quiz from a class mean of 60% to 84% (p < .001). Residents also exhibited an increase in self-reported confidence in managing patients with inappropriately firing defibrillators (p < .001) and in knowing when to place a magnet over a patient's defibrillator (p < .001). Discussion Residents demonstrated increased knowledge of defibrillator function as well as increased confidence in managing patients with malfunctioning defibrillators after participating in this simulation experience.